2014
DOI: 10.1080/13102818.2014.924683
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective effect ofRapana thomasianahemocyanin in gamma induced acute radiation syndrome

Abstract: The radioprotective effect of Rapana thomasiana hemocyanin (RtH) against radiation-induced injuries (stomach ulcers, survival time and endogenous haemopoiesis) and post-radiation recovery was investigated in male albino mice (C3H strain). Radiation course was in a dose of 7.5 Gy (LD 100/30 – dose that kills 100% of the mice at 30 days) from 137Cs with a dose of 2.05 Gy/min. Radiation injuries were manifested by inducing а hematopoietic form of acute radiation syndrome. RtH was administered intraperitoneally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…In the present study, MLA improved the survival rates of mice after exposure to a lethal dose of radiation, confirming that MLA provided protection against radiation injury [ 28 , 29 ]. Hematopoietic injury is one of the most important side effects of radiation syndrome [ 30 , 31 ]; therefore, we investigated the effects of MLA on the hematopoietic system using an established mouse model [ 14 ].…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, MLA improved the survival rates of mice after exposure to a lethal dose of radiation, confirming that MLA provided protection against radiation injury [ 28 , 29 ]. Hematopoietic injury is one of the most important side effects of radiation syndrome [ 30 , 31 ]; therefore, we investigated the effects of MLA on the hematopoietic system using an established mouse model [ 14 ].…”
Section: Discussionsupporting
confidence: 76%
“…To date, there are still a limited number of chemical RAs clinically used to minimize the severity and duration of toxicities associated with radiotherapy. Some other agents such as palifermin [121] , genistein [122] , angiotensin I-converting enzyme inhibitors [123] , melanin [124] , hemocyanin [125] and Vitamin D [126] showed a promising effect against the radiation toxicity, however there is a lack of high quality clinical studies for most of the agents described. The evaluation of safety and efficacy of these emerging agents are needed and their effects on tumor sensitivity should be verified [117] .…”
Section: Ra Its Categoris and Mechanisms Of Functionmentioning
confidence: 99%
“…Oxidative stress, lipid peroxidation, DNA breaks, and p53/ NF-κB activities have been previously studied in animal models after exposure to gamma radiation [82,83]. It has previously been demonstrated that death of mice occurred after 137 Cs [84] and 60 Co gamma radiation [82,85,86]. Our study also observed 80% animal death at 30 days after exposure to radiation of 6.4 Gy using 137 Cs as an irradiating source, and post-treatment with celastrol for 30 days significantly increased the mouse survival rate after whole-body gamma irradiation exposure.…”
Section: Discussionmentioning
confidence: 99%